RECONSTRUCTION OF MARRIAGE AGREEMENTS IN INDONESIA - Lenny Guspidawati; Jumni Nelli; Raahman Alwi; Suja'i Sarifandi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The implementation of prenuptial agreements in Indonesia remains a frequent source of debate, particularly regarding the time limit for drafting them, the validity of the separation of assets, and third-party protection, which are not fully aligned with societal dynamics. This study aims to analyze the legal status and reconstruct or review the regulations on prenuptial agreements. The goal is to make the regulations more responsive to justice and protect the rights of all parties. The reconstruction of marriage agreements in Indonesia refers to the process of refining or reinterpreting legal provisions related to premarital agreements or postnuptial agreements, with the aim of enhancing the protection of individual rights, particularly for women, and avoiding potential conflicts within the family. This is based on Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI), and Constitutional Court Decision Number 69/PUU-XIII/2015, which reformed the boundaries of agreements to be more inclusive and proportional. This reconstruction emphasizes the principles of legal certainty, gender equality, and adaptation to modern social dynamics, including the impact of globalization and changing cultural values. The reconstruction of marriage agreements following Constitutional Court Decision Number 69/PUU-XIII/2015 confirms that separation of assets agreements can be made both before and during marriage without requiring court approval. This legal instrument serves to protect inherited assets and facilitate mixed marriages, with the mandatory requirement that they be drawn up through a notarial deed to ensure legal certainty and third-party protection. It is recommended that implementing regulations be revised, registration procedures be improved, and notaries play a more vigilant role in ensuring good faith and asset details.